Analysis Of The Influence Of Brand Equity And Social Media On Revisit Decision With Intention To Revisit As A Mediation Variable In Yarsi Teeth And Mouth Hospital - Ilham Arief; Muslikh, Muslikh; Hulmansyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This research aims to provide a deeper analysis of the complex relationship between brand equity, social media, interest in revisiting, and the decision to revisit in the context of hospital services. Quantitative techniques are used in this study together with cross-sectional data gathering. Everybody in the population is a patient. This study uses non-probability sampling to acquire data. The study's sample comprised one hundred participants. A questionnaire was utilized to collect data. The SEM-PLS analytical method will be used to process the data. The study's findings support the notion that social media and brand equity positively and significantly impact both the desire to return and the decision to do so. It should be highlighted, nonetheless, that the desire to return does not necessarily affect the choice to return. In addition, although interest in returning to visit does not mediate the relationship between brand equity and the decision to visit again, this interest does mediate the relationship between social media and the decision to visit again. This shows that the influence of social media can make it easier for consumers to obtain information, thereby increasing their chances of returning to the hospital for treatment. To increase interest in repeat visits, it is necessary to organize intensively so that the hospital service brand becomes stronger in the eyes of consumers.